Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s11538-013-9827-4
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Pattern Formation and Spontaneous Polarisation: The Linear Noise Approximation and Beyond

Abstract: We review the mathematical formalism underlying the modelling of stochasticity in biological systems. Beginning with a description of the system in terms of its basic constituents, we derive the mesoscopic equations governing the dynamics which generalise the more familiar macroscopic equations. We apply this formalism to the analysis of two specific noiseinduced phenomena observed in biologically-inspired models. In the first example, we show how the stochastic amplification of a Turing instability gives rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
152
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(157 citation statements)
references
References 31 publications
2
152
0
3
Order By: Relevance
“…26 As is discussed in Introduction, recent numerical studies support the validity of chemical Fokker-Planck equation up to smaller value of Ω than the range adopted for LNA. 7,31,32 In fact, we also demonstrated that the direct numerical simulations agree quite well with the predictions of chemical Fokker-Planck equation for all motifs marked by "+" or "++" in Fig. 1, where small-number effects are well reproduced by the chemical Fokker-Planck equation, rather than by the LNA.…”
Section: Discussionsupporting
confidence: 78%
“…26 As is discussed in Introduction, recent numerical studies support the validity of chemical Fokker-Planck equation up to smaller value of Ω than the range adopted for LNA. 7,31,32 In fact, we also demonstrated that the direct numerical simulations agree quite well with the predictions of chemical Fokker-Planck equation for all motifs marked by "+" or "++" in Fig. 1, where small-number effects are well reproduced by the chemical Fokker-Planck equation, rather than by the LNA.…”
Section: Discussionsupporting
confidence: 78%
“…For further background on how to arrive precisely at the forms given by Eq. (3) the reader is referred to previous discussions in the literature [1,6,43]. If W (1) and W (2) are independent of n, then the selection is known as frequency independent selection.…”
Section: Setting-up the Modelmentioning
confidence: 99%
“…In a previous paper [43], we have reviewed the process of setting-up a description of this class of biological systems in terms of its basic constituents, and from this deriving the mesoscopic equations governing the dynamics which generalise what might be the more familiar macroscopic equations. In particular, in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, new effective extrema may be formed through the effects of noise [36], as well as the effective location of extrema being moved. In the present case, the effect is more closely related to the situation found in some kinds of stochastic pattern formation [37,38], where the region of stability of patterns can be increased by the stochastic effects giving a new effective condition for stability which differs from that found through a purely deterministic analysis.…”
Section: Discussionmentioning
confidence: 51%